2009
DOI: 10.1540/jsmr.45.187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four different .ALPHA.1-adrenoceptor antagonists on .ALPHA.-adrenoceptor agonist-induced contractions in isolated mouse and hamster ureters

Abstract: Purpose: To compare the efficacy of the selective α1A-adrenoceptor antagonist silodosin with those of doxazosin, terazosin, and alfuzosin against α-adrenoceptor agonist-induced contractions in mouse and hamster ureters. Methods: The four α1-adrenoceptor antagonists were evaluated against norepinephrine-induced phasic contractions in mouse isolated ureteral preparations and against phenylephrine-induced sustained contractions in hamster isolated ureteral preparations using a functional experimental technique. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This was clearly demonstrated previously (2). Alpha receptors were found to be mediating ureteral contractions in rat models (3). As this was demonstrated in rat models, human researchers used this as a model before human research.…”
Section: Discussionsupporting
confidence: 62%
“…This was clearly demonstrated previously (2). Alpha receptors were found to be mediating ureteral contractions in rat models (3). As this was demonstrated in rat models, human researchers used this as a model before human research.…”
Section: Discussionsupporting
confidence: 62%
“…They found that silodosin dose dependently suppressed the phenylephrine‐induced increase in intravesical ureteral pressure, but decreased the mean blood pressure only at higher doses. In contrast, naftopidil decreased mean blood pressure at the same doses as those that phenylephrine‐induced increase in intravesical ureteral pressure . Therefore, conversely to other α1‐ARs blockers, silodosin may facilitate distal ureteral stone passage without reaching potential hypotensive doses.…”
Section: How To Get the Most Out Of Silodosin: From The Critical Analmentioning
confidence: 88%
“…Kobayashi et al. compared the effects of silodosin vs. naftopidil on intraureteral pressure in anesthetised dogs . They found that silodosin dose dependently suppressed the phenylephrine‐induced increase in intravesical ureteral pressure, but decreased the mean blood pressure only at higher doses.…”
Section: How To Get the Most Out Of Silodosin: From The Critical Analmentioning
confidence: 99%
“…31 It was revealed that 10 mg/kg alfuzosin treatment of rats with erectile dysfunction and partial bladder outlet obstruction has antioxidant effect, restored NO release, and decreased sympathomimetic effecs. 12 Besides its aforementioned effect of reducing the pressure on the urinary system, it is thought that alfuzosin provides protective benefits on kidneys and the RAA system with its antioxidant efficiency and by decreasing the sympathicomimetic tonus.…”
Section: Discussionmentioning
confidence: 99%